Epidemiology of Takayasu arteritis in Shanghai: A hospital‐based study and systematic review. (27th July 2021) - Sun, Ying; Yin, Meng‐meng; Ma, Li‐li; Dai, Xiao‐min; Lv, Liang‐jing; Chen, Xiao‐xiang; Ye, Shuang; Li, Ting; Chen, Jie; Zhao, Dong‐bao; Kong, Rui‐na; Wei, Qiang‐hua; et al.
Abstract: Background: Takayasu arteritis (TAK) is a rare large vessel vasculitis, and epidemiological data on TAK are lacking in China. Thus, we designed this study to estimate the TAK prevalence and incidence in residential Shanghai, China. Methods: Data on diagnosed TAK cases aged over 16 years were retrieved from 22 tertiary hospitals in Shanghai through hospital electronic medical record systems between January 1, 2015 and December 31, 2017 to estimate the prevalence and incidence. A systematic literature review based on searches in PubMed, Ovid‐Medline, Excerpta Medica Database (EMBASE), Web of Science, and China National Knowledge Infrastructure (CNKI) was performed to summarize TAK distribution across the world. Results: In total 102 TAK patients, with 64% female, were identified. The point prevalence (2015‐2017) was 7.01 (95% CI 5.65‐8.37) cases per million, and the mean annual incidence was 2.33 (1.97‐3.21) cases per million. The average age of TAK patients was 44 ± 16 years, with the highest prevalence (11.59 [9.23‐19.50] cases per million) and incidence (3.55 [0.72 3.74] cases per million) in the 16 to 34 years population. Seventeen reports were included in the system review, showing that the epidemiology of TAK varied greatly across the world. The incidence and prevalence were both relatively higher in Asian countries, with the prevalence ranging 3.3‐40 cases per million and annual incidence ranging 0.34‐2.4 cases per million. Conclusions: The prevalence and incidence of TAK in Shanghai was at moderate to high levels among the previous reports. The disease burden varied globally among racial populations.